The effectiveness of the sports training environment on the physical development of female students at Thai Nguyen university of education in Vietnam - Nguyen, Nhac; Duc, Tuan Ma; Thi, Tu Tran (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to evaluate the impact of the sports training environment on the physical development of female students at Thai Nguyen University of Education in Vietnam after a 12-week intervention. Seventy-four healthy female students were randomly selected and divided into two groups: an experimental group, which participated in a structured physical training environment, and a control group, which engaged in self-directed training. Five fitness criteria were used to assess physical development: the 30-meter sprint test (to measure speed), the standing long jump test (to measure explosive leg power), the 30-second sit-up test (to assess core strength), the 4×10-meter shuttle run test (to evaluate agility), and a 5-minute endurance run test (to assess endurance). After 12 weeks of physical training in an enhanced environment, the experimental group demonstrated higher improvements across all five fitness tests compared to the control group. In the experimental group, the most significant improvements were observed in the 30-second sit-up test (31.35%), standing long jump (12.85%), 5-minute endurance run (11.21%), 30-meter sprint (6.69%), and 4×10-meter shuttle run (6.33%). This study has shown that the sports training environment has a strong influence on the physical development of female students. Universities should consider and recommend enhancing training environments as a measure to improve both the academic performance and physical development of students.